Mumarasah al-Ta'lim al-Musagar li Tarqiyah Maharah al-Kalam fi Syu'bah Ta'lim al-Lugah al-Arabiyah - Ana Konita; Ahmad Kamil Fadoli (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2021)
As it is known that micro-teaching at the Islamic University of Jember is carried out through